2020
DOI: 10.1002/cmdc.201900735
|View full text |Cite
|
Sign up to set email alerts
|

Yicathins B and C and Analogues: Total Synthesis, Lipophilicity and Biological Activities

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Total synthesis of xanthone derivatives has been reported due to the trace isolation yield of certain xanthones from natural sources. The total synthesis of termicalcicolanone A, α-mangostin, and mangiferin has been reported recently [90][91][92][93].…”
Section: Synthesis Of Xanthone Derivativesmentioning
confidence: 99%
“…Total synthesis of xanthone derivatives has been reported due to the trace isolation yield of certain xanthones from natural sources. The total synthesis of termicalcicolanone A, α-mangostin, and mangiferin has been reported recently [90][91][92][93].…”
Section: Synthesis Of Xanthone Derivativesmentioning
confidence: 99%
“…To complement the information disclosed, the pharmacokinetic parameters were evaluated in this document using the SWISSADME platform [59]. Based on the analyses of Table 1, it may be concluded that more than half of the isolated marine compounds (1-6, 9, 20-22, 29-41, 43-46) follow Lipinski rules [60], but only ten (5,27,29,38,40,41,(43)(44)(45)(46) are predicted to have high BBB permeability.…”
Section: Adme Propertiesmentioning
confidence: 99%
“…Based on the analyses of Table 1 , it may be concluded that more than half of the isolated marine compounds ( 1 – 6 , 9 , 20 – 22 , 29 – 41 , 43 – 46 ) follow Lipinski rules [ 60 ], but only ten ( 5 , 27 , 29 , 38 , 40 , 41 , 43 – 46 ) are predicted to have high BBB permeability.…”
Section: Adme Propertiesmentioning
confidence: 99%
“…These xanthones are usually highly substituted, with different substituent patterns being the substituents found to be essential for four types; hydroxy, methoxy, methyl, and methoxycarbonyl groups. It seems that the methoxy group is not common in bioactive marine xanthones [ 50 ], but yicathins B ( 3 ) and C ( 4 ) ( Figure 2 ), which were recently prepared by total synthesis [ 51 ], present such a group at C-8. Other examples include xanthones bearing a 6-methoxy group ( 2 ) and ( 6 ) and 7-methoxy group ( 13 ) and ( 15 ) ( Figure 2 ).…”
Section: New Marine Xanthones Isolated Since 2010mentioning
confidence: 99%